The effect of radiation on entropy and heat transfer of MHD nanofluids inside a quarter circular enclosure with a changing L-shaped source: lattice Boltzmann methods. Issue 5 (4th May 2023) - Khan, Farhan; Xiao-Dong, Yang; Aamir, Nudrat; Saeed, Tareq; Ibrahim, Muhammad
Abstract: Simulations of free convective heat transfer (HT) and entropy generation ( S Gen ) in a closed enclosure are carried out in this research. Tc is the temperature of the enclosure's top circular wall. A piece of the enclosure's left wall ( L ) and a section of the enclosure's right wall ( H ) are both at Th . The remainder of the walls are insulated. A constant volumetric radiation ( Rd ) is produced within the cavity. In relation to the horizon, the enclosure is at 45° angle. The equations are solved using the lattice Boltzmann method (LBM). The thermal conductivity of nanofluids (NFs) was also calculated using a model based on empirical data. The following findings are obtained by varying the Ha, the length of the heated walls, and the angle of the magnetic field (MaF). An increase in Ha lowers the quantity of Nu on both heated walls and weakens the fluid flow in the enclosure. The HT rate is increased by increasing the length of heated walls. The quantity of HT from hot walls varies depending on the angle of the MaF. The quantity of HT from one of the hot walls may be larger depending on the angle of the MaF. An increment in the angle of the magnetic field from 0 to 60° enhances the Nusselt number by 10.3%.